Stabilization of Soft Soil by a Sustainable Binder Comprises Ground Granulated Blast Slag (GGBS) and Cement Kiln Dust (CKD) - Ruqayah Al-Khafaji; Anmar Dulaimi; Hassnen Jafer; Nuha S. Mashaan; Shaker Qaidi; Zahraa Salam Obaid; Zahraa Jwaida (Recycling, 2023)
Due to its significant deficiencies such as low permeability, low bearing and shear strength, and excessive compressibility, soft soil is one of the most problematic types of soil in civil engineering and soil stabilization can be considered a suitable technique for pavements. This study investigates the use of ground granulated blast slag (GGBS) and cement kiln dust (CKD) as stabilizers for soft soil. Thus, this study involves two optimization stages; in the first stage, GGBS was incorporated into 0%, 3%, 6%, 9%, and 12% by the weight of cement to obtain the optimal percentage, which was 6%. Then, the optimal GGBS was blended with CKD in a binary system at 0%, 25%, 50%, 75%, and 100% by the dry weight of the soil. The testing program used in this paper was Atterberg limits with compaction parameters to investigate the physical properties and unconfined compressive strength (USC) at 7 and 28 days to examine the mechanical characteristics. In addition, the microstructures of the soil specimens were tested at 7 and 28 days using scanning electron microscopy (SEM). The findings reveal that the binary system enhanced the physical and mechanical properties of the soft soil. The optimum binder achieved in this study was 6% (25% GGBS and 75% CKD), which generates an increase in strength of about 3.3 times in 7 days, and of 5.5 times in 28 days in comparison to the untreated soil. The enhancement was attributed to the formation of the hydration products as approved by SEM. Consequently, in the case of soft subgrade soils, this technique can increase the pavement’s bearing capacity and performance.